2012
DOI: 10.1177/0267659112456894
|View full text |Cite
|
Sign up to set email alerts
|

In vitro clearance of dexmedetomidine in extracorporeal membrane oxygenation

Abstract: Dexmedetomidine (DMET) is a useful agent for sedation, both alone and in combination with other agents, in critically ill patients, including those on extracorporeal membrane oxygenation (ECMO) therapy. The drug is a clonidine-like derivative with an 8-fold greater specificity for the alpha 2-receptor while maintaining respiratory and cardiovascular stability. An in vitro ECMO circuit was used to study the effects of both "new" and "old" membrane oxygenators on the clearance of dexmedetomidine over the course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 42 publications
(63 reference statements)
2
73
1
1
Order By: Relevance
“…Our findings do not necessarily mean that ECMO use will not result in greater sedative requirements; rather, other important factors also exist that will influence the amount of sedation required to reach the maximum desired sedation goal in this population. The effect of ECMO on the pharmacokinetics and pharmacodynamics of sedation therapy is complex . Future prospective studies that investigate the response to sedation during ECMO should be time dependent and incorporate these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings do not necessarily mean that ECMO use will not result in greater sedative requirements; rather, other important factors also exist that will influence the amount of sedation required to reach the maximum desired sedation goal in this population. The effect of ECMO on the pharmacokinetics and pharmacodynamics of sedation therapy is complex . Future prospective studies that investigate the response to sedation during ECMO should be time dependent and incorporate these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Three ex vivo studies using adult ECMO circuits composed of PVC tubing and a hollow polymethylpentene fiber membrane oxygenator demonstrated significant losses of commonly used opioids and sedatives [6, 18, 19]. One investigation observed as much as a 93% loss in dexmedetomidine concentrations at 24 h [18].…”
Section: Analgesia and Sedationmentioning
confidence: 99%
“…One investigation observed as much as a 93% loss in dexmedetomidine concentrations at 24 h [18]. Another study, measuring concentrations of morphine, fentanyl, and midazolam over a 24‐hour period, demonstrated that the average drug recovery relative to baseline was lower with lipophilic drugs [6].…”
Section: Analgesia and Sedationmentioning
confidence: 99%
“…When targeting light levels of sedation or weaning other sedatives, dexmedetomidine may be the preferred agent. Given dexmedetomidine's high level of lipophilicity (log p = 2.8) and high level of protein binding (94–97%) and known sequestration within ECLS circuits, higher than normal doses may be needed to achieve the desired level of sedation …”
Section: Specific Ecls Management Considerationsmentioning
confidence: 99%